Efficacy and safety of small-incision corneal intrastromal lenticule implantation for hyperopia correction: a systematic review and meta-analysis - Wang, Yue; Zheng, Jingjing; Guo, Zuofeng; Fang, Xuejun (Frontiers in Medicine, 2024)
Purpose: To assess the efficacy and safety of intrastromal lenticule implantation for the treatment of hyperopia.Methods: A systematic search of PubMed, Web of Science, Embase, Cochrane Library, China National Knowledge Internet, and Wan Fang Database identified studies on small-incision intrastromal lenticule implantation for hyperopia correction until January 2023.The Joanna Briggs Institute (JBI) critical appraisal tool was used to assess the quality of the retrospective research, and the Methodological Index for Non-randomized Studies (MINORS) was used to assess the quality of the prospective research. This study included postoperative visual outcomes, corneal morphology, and biomechanical outcomes.Results: A total of 456 articles were identified, of which 10 were included in the meta-analysis. Ten single-arm studies involving 190 eyes were included. A meta-analysis demonstrated that corneal intrastromal lenticule implantation treatment significantly improved hyperopia. Uncorrected distance visual acuity (UDVA) significantly improved compared to the preoperative value (P= 0.027), corrected distance visual acuity showed no difference compared to the preoperative value (P = 0.27), and 87% eyes have no loss of one or more lines in the Snellen lines of CDVA(P＜0.00001). There was a significant difference between the spherical equivalent refractive (SE) and preoperative examination (P＜0.00001),52% of eyes had ±0.5 diopters (D) postoperative SE (P＜0.00001), and 74% eyes had ±1.0 D postoperative SE (P＜0.00001). The central corneal thickness (CCT) increased by 72.68 μm compared to that preoperatively (P＜0.00001),and corneal curvature increased by 4.18D (P＜0.00001). The Q-value decreased by 0.82 (P＜0.00001), and higher-order aberration (HOA) decreased by 0.66 (P＜0.00001). Conclusions: Small-incision intrastromal lenticule implantation may be an effective solution for correcting hyperopia. The effect of improved vision is significant, but further exploration is needed for changes in corneal biomechanics and long-term safety.